China's Pattern of Trade and Growth after WTO Accession : Lessons for Other Developing Countries - Zhao, Longyue; Wang, Yan (2012)
World Trade Organization (WTO) accession marked a new beginning for China's economic, legal and institutional reforms and rapid integration with the rest of the world. The purpose of this paper is to review China's post-WTO transition experience, synthesize and update studies on China's pattern of trade and structural transformation, and provide both positive and negative lessons for other developing countries. The paper has broadly reviewed the latest policy changes after China's WTO accession, and literatures on China's trade and economic development issues in order to understand the Chinese success and its speciality, and draw some useful lessons for both China's decision-makers and other developing countries. There are two main findings: first, market liberalization alone is not sufficient, and economic system reform and the liberalization are closely related and complement and promote each other. Second, experimentations via special economic zones (SEZs) and opening to foreign direct investment (FDI), which facilitated and supported cluster development and learning-by-doing, are needed for industrial upgrading and export competitiveness.